2009
DOI: 10.1007/s12011-009-8413-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Maternal Exposure of Fluoride on Biometals and Oxidative Stress Parameters in Developing CNS of Rat

Abstract: Excessive intake of essential elements agitates elemental homeostasis resulting in their heterogeneous distribution. Distraction of these elements in central nervous system (CNS) have been demonstrated in many neurological disorders, which are vital in generating free radicals, causing oxidative stress, and contributing to neuronal maladies. The developing CNS is highly vulnerable to environmental agents, including fluoride. Fluorosis is one such disorder ensued from excessive consumption of fluoride containin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 30 publications
4
11
0
Order By: Relevance
“…Zinc acts as an important antioxidant in BBB membrane stability and offering protection to membrane protein thiol groups [43], also involved in brain phospholipid metabolism [44]. The supplementation of zinc in the present study augmented its depleted levels in brain which was observed in our previous study during pre and post-natal fluoride exposure [25]. F interacts with zinc binding sites on an important DNA associated protein called protamine.…”
Section: Groupsupporting
confidence: 61%
See 2 more Smart Citations
“…Zinc acts as an important antioxidant in BBB membrane stability and offering protection to membrane protein thiol groups [43], also involved in brain phospholipid metabolism [44]. The supplementation of zinc in the present study augmented its depleted levels in brain which was observed in our previous study during pre and post-natal fluoride exposure [25]. F interacts with zinc binding sites on an important DNA associated protein called protamine.…”
Section: Groupsupporting
confidence: 61%
“…Physiologically the brain uses over 20% of the body oxygen and generates very large levels of ROS as it has poor endogenous antioxidant defense system and relies on the dietary intake of antioxidants. The ingestion of excessive F in this study significantly decreased animal (mother) growth symptomised by depressed appetite leading to the poor growth rate in pups [25]. This is because F may result in primary malnutrition by displacing other nutrients (minerals/elements) in the diet.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…In this study, fluoride treatment increased LP and NO production, whereas the estimated antioxidant parameters were diminished in red blood cells and in examined heart and brain tissues. These results suggested that the balance between the oxidative system and anti-oxidant system in the rats was out of order during fluoride exposure (Narayanaswamy & Piler, 2010). The present findings are in harmony with recent observations by Inkielewicz-Stepniak and Czarnowski (2010), indicating that the excessive fluoride exposure can induce LP, specifically polyunsaturated fatty acids.…”
Section: Discussionsupporting
confidence: 92%
“…Epidemiological investigations indicated that long-term high-level fluoride intake can lead to severe damage in the metabolism of many systems and organs in animals and humans (Hassan & Yousef, 2009). Recent studies suggest that increased generation of ROS and enhanced LP have been shown to play an important role in fluorosis (Narayanaswamy & Piler, 2010).…”
Section: Introductionmentioning
confidence: 99%